Characterization of angiosperm nrDNA polymorphism, paralogy, and pseudogenes. - Bailey, C; Carr, T; Harris, S; Hughes, C (2003)
Many early reports of ITS region (ITS 1, 5.8S, and ITS 2) variation in flowering plants indicated that nrDNA arrays within individuals are homogeneous. However, both older and more recent studies have found intra-individual nrDNA polymorphism across a range of plant taxa including presumed non-hybrid diploids. In addition, polymorphic individuals often contain potentially non-functional nrDNA copies (pseudogenes). These findings suggest that complete concerted evolution should not be assumed when embarking on phylogenetic studies using nrDNA sequences. Here we (1). discuss paralogy in relation to species tree reconstruction and conclude that a priori determinations of orthology and paralogy of nrDNA sequences should not be made based on the functionality or lack of functionality of those sequences; (2). discuss why systematists might be particularly interested in identifying and including pseudogene sequences as a test of gene tree sampling; (3). examine the various definitions and characterizations of nrDNA pseudogenes as well as the relative merits and limitations of a subset of pseudogene detection methods and conclude that nucleotide substitution patterns are particularly appropriate for the identification of putative nrDNA pseudogenes; and (4). present and discuss the advantages of a tree-based approach to identifying pseudogenes based on comparisons of sequence substitution patterns from putatively conserved (e.g., 5.8S) and less constrained (e.g., ITS 1 and ITS 2) regions. Application of this approach, through a method employing bootstrap hypothesis testing, and the issues discussed in the paper are illustrated through reanalysis of two previously published matrices. Given the apparent robustness of the test developed and the ease of carrying out percentile bootstrap hypothesis tests, we urge researchers to employ this statistical tool. While our discussion and examples concern the literature on plant systematics, the issues addressed are relevant to studies of nrDNA and other multicopy genes in other taxa.